2014
DOI: 10.2141/jpsa.0130017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lutein Sources on Lutein-Enriched Egg Production and Hepatic Antioxidant System in Laying Hens

Abstract: The present study was conducted to investigate the effects of two dietary lutein sources such as the commercial lutein and the emulsified crude extract of spinach containing lutein on the transfer of lutein into egg yolks as well as the antioxidant defense system in the liver of laying hens. A total of thirty-six, 24-week-old White leghorn hens were randomly assigned to a basal diet (CON) and that supplemented with a commercial lutein (LUT, 40 mg lutein /kg of diet) and the crude extract of spinach dissolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(29 reference statements)
2
3
0
1
Order By: Relevance
“…In particular, there was a significant interaction between the effects of breed and diet on lutein content, which showed that the combination of MA dietary treatment and the SF breed resulted in a higher accumulation of lutein in the yolk. Feeding lutein to laying hens enhances hepatic SOD activity (Jang et al, 2014), while feeding them with lycopene increases yolk oxidative stability (An et al, 2019). The present study revealed similar findings, although the carotenoid types were dissimilar.…”
Section: Discussionsupporting
confidence: 79%
“…In particular, there was a significant interaction between the effects of breed and diet on lutein content, which showed that the combination of MA dietary treatment and the SF breed resulted in a higher accumulation of lutein in the yolk. Feeding lutein to laying hens enhances hepatic SOD activity (Jang et al, 2014), while feeding them with lycopene increases yolk oxidative stability (An et al, 2019). The present study revealed similar findings, although the carotenoid types were dissimilar.…”
Section: Discussionsupporting
confidence: 79%
“…reported an increase in egg yolk color from 6.4 to 13.1 ( P < 0,001) by supplementation of 250 mg kg −1 lutein to laying hens' feed, while Englmaierová and Skřivan supplemented 100 mg kg −1 lutein to hens' feed and achieved an increase in egg yolk color from 7.7 in the control to 8.4 ( P < 0.001). Jang et al . confirmed that supplementation of even small amounts of lutein (40 mg kg −1 ) affected egg yolk color ( P < 0.05).…”
Section: Discussionmentioning
confidence: 89%
“…Others manuscripts show the importance of a balance between the production and elimination of free radicals for a good productive performance of birds in posture [ 31 , 32 , 33 ]. We did not observe any improvement in the percentage of posture due to cinnamon supplementation; however, animals fed cinnamon supplementation presented better conversion by egg mass.…”
Section: Discussionmentioning
confidence: 99%